Peripheral Amyloid Precursor Protein Derivative Expression in Fragile X Syndrome - McLane, Richard D.; Schmitt, Lauren M.; Pedapati, Ernest V.; Shaffer, Rebecca C.; Dominick, Kelli C.; Horn, Paul S.; Gross, Christina; Erickson, Craig A. (Frontiers in Integrative Neuroscience, 2019)
Fragile X syndrome (FXS) is the most common inherited form of intellectual disability and is associated with increased risk for autism spectrum disorder (ASD), anxiety, ADHD, and epilepsy. While our understanding of FXS pathophysiology has improved, a lack of validated blood-based biomarkers of disease continues to impede bench-to-bedside efforts. To meet this demand, there is a growing effort to discover a reliable biomarker to inform treatment discovery and evaluate treatment target engagement. Such a marker, amyloid-beta precursor protein (APP), has shown potential dysregulation in the absence of fragile X mental retardation protein (FMRP) and may therefore be associated with FXS pathophysiology. While APP is best understood in the context of Alzheimer disease, there is a growing body of evidence suggesting the molecule and its derivatives play a broader role in regulating neuronal hyperexcitability, a well-characterized phenotype in FXS. To explore the viability of APP as a peripheral biological marker in FXS, we conducted a comprehensive ELISA-based evaluation of plasma APP-related species involving 27 persons with FXS (mean age: 22.0±11.5) and 25 age- and sex-matched persons with neurotypical development (mean age: 21.1±10.7). Peripheral levels of both Aβ(1-40) and Aβ(1-42) were increased, while sAPPα was significantly decreased in persons with FXS as compared to control participants. These results suggest that dysregulated APP processing, with potential preferential β-secretase processing, may be a readily accessible marker of FXS pathophysiology.